2008
DOI: 10.2174/1874143600802010054
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Pharmacological Activities of Antidepressants: A Novel Approach

Abstract: Antidepressants have different receptor binding profiles, which are related to therapeutic action and adverse drug reactions. We constructed a model to classify antidepressants on the basis of their binding properties of most common transporter-and receptor sites. Receptor binding was quantified by calculating receptor occupancy for the 5-HT (serotonin) reuptake transporter, norepinephrinic reuptake transporter, 5-HT 2C -receptor, M 3 -receptor, H 1 -receptor and 1 -receptor. To identify groups of antidepressa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 10 publications
(11 reference statements)
4
36
0
1
Order By: Relevance
“…In that study, hyperglycemia was most pronounced in antidepressants with binding properties for the 5-HT 2c receptor (serotonin), H 1 -receptor (histamine), and norepinephrinic reuptake transporter [9,10]. In contrast, hypoglycemia was most pronounced in antidepressants with binding properties for the serotonin reuptake transporter [9,10]. In another study, antidepressants with a high affinity for the serotonin reuptake transporter were associated with a trend toward increased risk for hypoglycemia (OR = 1.37; 95% CI: 0.71-2.62) [8].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In that study, hyperglycemia was most pronounced in antidepressants with binding properties for the 5-HT 2c receptor (serotonin), H 1 -receptor (histamine), and norepinephrinic reuptake transporter [9,10]. In contrast, hypoglycemia was most pronounced in antidepressants with binding properties for the serotonin reuptake transporter [9,10]. In another study, antidepressants with a high affinity for the serotonin reuptake transporter were associated with a trend toward increased risk for hypoglycemia (OR = 1.37; 95% CI: 0.71-2.62) [8].…”
Section: Discussionmentioning
confidence: 88%
“…Although no clear pattern between antidepressant class (i.e., tricyclic antidepressants [TCAs], selective serotonin reuptake inhibitors [SSRI], serotonin-norepinephrine reuptake inhibitors [SNRIs], and other antidepressants) and hyperglycemia or hypoglycemia was observed in this review of case reports, the study by Derijks et al showed that the propensity to cause hyperglycemia or hypoglycemia was dependent on the pharmacological properties of individual antidepressant agents (see ''Appendix'') rather than a class effect [49,50]. In that study, hyperglycemia was most pronounced in antidepressants with binding properties for the 5-HT 2c receptor (serotonin), H 1 -receptor (histamine), and norepinephrinic reuptake transporter [9,10]. In contrast, hypoglycemia was most pronounced in antidepressants with binding properties for the serotonin reuptake transporter [9,10].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations